SHARIA GENERAL CONTRACT IN THE CONTEXT OF SHARIA INSURANCE IN INDONESIA - yamani, sudin; Amin, Fitria Hi Mhd (Universitas Muhammadiyah Surabaya, 2024)
This article aims to identify and study Islamic financial institutions, in this case, Islamic Insurance, which implements an economic system based on the contracts in Islamic Economics. This research is also the result of library research that includes a study of various written works, including books, journals, and others. This article is compiled based on original materials from laws and regulations and the Indonesian Ulema Council on Islamic insurance fatwas. To understand the existence of these contracts and the problems they cause, this article discusses general contracts such as the Tijarah contract and the Tabaru contract in Indonesian Islamic insurance. The Tabarru' and Tijarah contracts are used in Islamic insurance, as evidenced by the results of research based on laws, laws, and regulations, and fatwas issued by the Indonesian Ulema Council. The Tabarru contract is a grant contract, namely a contract that deposits several premiums. These premiums are grants from insurance participants, the purpose of which is as funds to help other insurance participants without expecting a profit. Meanwhile, the Tijarah contract is a premium marketing contract, where profit sharing is carried out by the provisions stipulated in the contract.